Laparoscopic -2port Varicocelectomy with Scarless Periumblical Mini-Incision: Initial Experience in Approach and Outcomes - Seo, Won Ik; Kwon, Jong Kyou; Kang, Pil Moon; Kim, Wansuk; Yoon, Jang Ho; Kim, Taek Sang; Chung, Jae Seung; Oh, Cheol Kyu (Urology Journal, 2018)
Purpose: As with other areas, there have been many efforts for minimally invasive surgery in varicocelectomy. We present our initial experience with laparoscopic varicocelectomy with a two-port scarless periumbilical mini-incision. Materials and Methods: The study enrolled 18 patients who underwent laparoscopic varicocelectomy with a twoport scarless periumbilical mini-incision from February 2012 to April 2013. The laparoscopic varicocelectomy was performed using two 5-mm ports at periumbilical sites in skin creases. Here, the surgical procedure is introduced and the outcomes of the case series are summarized. We reviewed other laparoscopic techniques and compared them with our technique. Results: The mean patient age was 34.8 years. Of the 18 patients, 15 had grade 3 varicoceles. The mean operating time was 62.5 minutes. Postoperatively, the scrotal pain level decreased immediately from a mean VAS score of 6.3 to 4.4 and then to 1.7 by 24 hours postoperatively. The mean hospital stay was 2.8 days. Complications included one hydrocele and two recurrent varicoceles. The operating time decreased as the surgeon’s experience increased. Conclusion: Laparoscopic varicocelectomy with a two-port scarless periumbilical mini-incision is a feasible technique that can be mastered relatively easily. Prospective and comparative studies are required to validate this new technique.